Investigation of Fragment Antibody Stability and Its Release Mechanism from Poly(Lactide‐co‐Glycolide)–Triacetin Depots for Sustained‐Release Applications. Issue 10 (22nd June 2015) - Chang, Debby P.; Garripelli, Vivek Kumar; Rea, Jennifer; Kelley, Robert; Rajagopal, Karthikan
<x xml:space="preserve">Abstract</x> Achieving long‐term drug release from polymer‐based delivery systems continues to be a challenge particularly for the delivery of large hydrophilic molecules such as therapeutic antibodies and proteins. Here, we report on the utility of an in situ‐forming and injectable polymer–solvent system for the long‐term release of a model antibody fragment (Fab1). The delivery system was prepared by dispersing a spray‐dried powder of Fab1 within poly(lactide‐co‐glycolide) (PLGA)–triacetin solution. The formulation viscosity was within the range 1.0 ± 0.3 Pa s but it was injectable through a 27G needle. The release profile of Fab1, measured in phosphate‐buffered saline (PBS), showed a lag phase followed by sustained‐release phase for close to 80 days. Antibody degradation during its residence within the depot was comparable to its degradation upon long‐term incubation in PBS. On the basis of temporal changes in surface morphology, stiffness, and depot mass, a mechanism to account for the drug release profile has been proposed. The unprecedented release profile and retention of greater than 80% of antigen‐binding capacity even after several weeks demonstrates that PLGA–triacetin solution could be a promising system for the long‐term delivery of biologics. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:3404–3417, 2015